Ulcerative colitis and its correlation with the incidence of colorectal cancer - Felix Ongko; Erwin Kurniawan Santosa; Edward Then; Lucky Anthonny Setiawan; Vivian Ongriana (Institute of Computer Science (IOCS), 2023)
The purpose of this research to further reviewed the pathogenesis, risk factors, screening, and preventive interventions for colorectal cancer associated with ulcerative colitis. The research method used descriptive qualitative through the Literature Review (LR) approach. The data source used a secondary source. Data analysis technique selects literature based on title, year, and indexed articles, then reviews articles that match the subject matter. A literature search was performed using databases, such as PubMed, Cochrane Library, and Science Direct. Colitis-associated neoplasia is thought to result from chronic inflammation, which induces changes in epithelial proliferation, survival, and migration through the effects of various chemokines and cytokines. The risk factors are in three main categories: disease-related, patient-related, and pathology-related. The most reliable screening test is colonoscopy, parallel with a structured endoscopic surveillance program that includes ongoing medical management for disease control. There are several chemopreventive options for the early prevention of colorectal cancer in cases of ulcerative colitis. In general, long-standing chronic inflammation in the intestinal mucosa increases the risk of colorectal cancer due to genetic and molecular alterations. Identifying high-risk groups and colonoscopic surveillance programs have been considered useful early detection measures.